Deteksi Dini Kesehatan Mental Emosional pada Mahasiswa - Sari, Melani Kartika; Susmiatin, Eko Arik (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2023)
Mental health is important for college students to be able to complete their academic assignments properly. In final year college students, Skripsi can be one of the causes of mental health problems. The purpose of this study was to describe emotional mental health in level 4 students of the Bachelor of Nursing Stikes Karya Husada, Kediri. This research is a quantitative research with descriptive analytic method. The population of this study were 4th level students of the Bachelor of Nursing Study Program Stikes Karya Husada Kediri, totaling 89 students. The sampling technique used was purposive sampling with 46 students as respondents. Data was collected using the SRQ 20 questionnaire which consisted of 20 question items for the detection of emotional mental health problems. Early detection of emotional mental health problems for students needs to be done to anticipate the occurrence of mental disorders due to the inability of students to cope with existing stressors.